Surface tension of corrosion inhibitor of carbon steel in hard water medium - Tety Sudiarti (Faculty of Mathematics and Natural Science, Universitas Negeri Yogyakarta, 2014)
Corrosion inhibition of carbon steel in hard water medium is very important because most of water for cooling and/or heating system needed in various industries is hard water and it is flown through pipes made of carbon steel. Before this, a research has been done concerning the effectiveness of inhibitors of thiourea and cimetidine as corrosion inhibitors in this medium. Here, a research has been done concerning the measurement of surface tension of thiourea and cimetidine to determine whether these inhibitors show properties similar to surfactants, hence indicate micellar phenomena. The Result of this research indicated that both thiourea and cimetidine are surfactants. The micellar critical concentration for both inhibitors is in accordance with the inhibitor concentration with optimal efficiency. Key words: surface tension, thiourea, cimetidine, surfactant